2006
DOI: 10.1038/sj.ijo.0803442
|View full text |Cite
|
Sign up to set email alerts
|

The new definition of metabolic syndrome by the international diabetes federation is less likely to identify metabolically abnormal but non-obese individuals than the definition by the revised national cholesterol education program: The Korea NHANES Study

Abstract: Objective: The new definitions for metabolic syndrome (MS) proposed by the IDF and revised NCEP have caused some confusion because patients have emerged that have satisfied the revised NCEP but not the IDF criteria. We performed this study to compare the prevalence of these criteria and to investigate the characteristics of discrepant cases. Research design and methods: A total of 7962 individuals aged X 20 years (3597 men; 4365 women) who participated in the 1998 Korean NHANES were included. We assessed the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
4
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 33 publications
5
49
4
1
Order By: Relevance
“…The IDF criteria did not identify 44.9% of men or 16.6% of women identified with the revised NCEP definition of metabolic syndrome in their data. 1 In our data, the IDF criteria also did not identify 40% of the men and 11% of the women identified with the revised NCEP definition of metabolic syndrome. 2 As for definitions of MS, Reaven 3 commented that the approach of WHO was the most rational effort, and the recent version of IDF was the most dangerous because approximately two-thirds of those in insulin-resistant tertile were either normal weight or overweight, and only about one-third of most insulinresistant persons were actually obese, and he subscribed a joint statement from the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD) 4 that the providers should avoid labeling patients with the term metabolic syndrome.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…The IDF criteria did not identify 44.9% of men or 16.6% of women identified with the revised NCEP definition of metabolic syndrome in their data. 1 In our data, the IDF criteria also did not identify 40% of the men and 11% of the women identified with the revised NCEP definition of metabolic syndrome. 2 As for definitions of MS, Reaven 3 commented that the approach of WHO was the most rational effort, and the recent version of IDF was the most dangerous because approximately two-thirds of those in insulin-resistant tertile were either normal weight or overweight, and only about one-third of most insulinresistant persons were actually obese, and he subscribed a joint statement from the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD) 4 that the providers should avoid labeling patients with the term metabolic syndrome.…”
contrasting
confidence: 58%
“…Yoon et al 1 reported that the revised National Cholesterol Education Program (NCEP) criteria seemed to be more appropriate for diagnosing metabolic syndrome (MS) given that the International Diabetes Federation (IDF) criteria could not identify high-risk patients who lacked central obesity but who nevertheless showed a clustering of metabolic risk factors. The IDF criteria did not identify 44.9% of men or 16.6% of women identified with the revised NCEP definition of metabolic syndrome in their data.…”
mentioning
confidence: 99%
“…15 Reports on the prevalence of metabolic syndrome from other populations are sometimes in agreement with our results and sometimes not. Although the prevalence of metabolic syndrome in a Korean population was similar to ours (metabolic syndrome prevalence for men was 14.2% according to the IDF criteria and 25.7% according to ATP III-modified criteria), 16 in Taiwan the prevalence of metabolic syndrome defined by ATP III-modified criteria was much higher (35.32% for men aged 40-64 years and 43.23% for men aged 65 years and over). In Asian Indians metabolic syndrome prevalence was reported to be 23.2%, 25.8%, and 18.3% according to WHO, IDF, and ATP III criteria, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…An earlier study among the Korean population showed that the IDF criteria failed to detect 44.9% of men and 16.6% of women with the metabolic syndrome identified by the revised NCEP/ATP criteria, because of the mis-identification of non-obese high-risk persons. 31 In our Japanese population, non-overweight persons with X2 risk factors constituted a large proportion of the population (24% in men and 19% in women). The PAFs for ischemic cardiovascular disease among non-overweight people with X2 risk factors were 20% in men and 14% in women, similar to or larger than those among overweight people with X2 risk factors.…”
Section: Discussionmentioning
confidence: 99%